Międzynarodowe standardy zamówień publicznych - wybrane aspekty - Tyrawa, Dominik (Przegląd Prawno-Ekonomiczny, 2007)
Streszczenie dostępne wyłącznie w języku angielskim: The author in the article describes selected regulations which concem Govemment Procurement all over the world. The author focuses on the presentation of Model Law on Procurement of Goods, Construction and Services with Guide to Enactment, International Bank for Resonstruction and Development Guidelines, Procurement dunder IBRD Loans and IDA Credit and World Trade Organization. What is more, the author emphasizes the most probable causes of those laws, general principles concerning Prequalification proceedings of Government Procurement and range of subjects and entities. The author briefly discusses some particular modes of Government Procurement which are present in mentioned laws. The main purpose of this article is to delve into the international standards of Government Procurement, underlining their positive aspects and positive influence on national regulations.